If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2b + 4) + -6b = 12 Reorder the terms: 3(4 + 2b) + -6b = 12 (4 * 3 + 2b * 3) + -6b = 12 (12 + 6b) + -6b = 12 Combine like terms: 6b + -6b = 0 12 + 0 = 12 12 = 12 Add '-12' to each side of the equation. 12 + -12 = 12 + -12 Combine like terms: 12 + -12 = 0 0 = 12 + -12 Combine like terms: 12 + -12 = 0 0 = 0 Solving 0 = 0 Couldn't find a variable to solve for. This equation is an identity, all real numbers are solutions.
| 2.5(2.5a+10)= | | -1135/-67 | | 6/21+25/7 | | 5x^2+-3xy+-2y^2=0 | | 3-5*8/9+15 | | (2x-1)=(x+4) | | y+3-4y=15 | | X^2+5/x=8 | | 8/1-7/10 | | 4/3m=1*3 | | 2p^2+8p-7=0 | | 1/3(x+3)=2 | | y=-5(1)+3 | | s^2+49=0 | | 2(n-1)+3-2x=7 | | 4n+4(2+2n)=26 | | 6(8-8p)=-6(1+9p) | | 76-A=44 | | 2^4-4*4.6/5 | | (136x+x)(x+64)= | | s^3-343=0 | | X-6=68 | | 2^4-4*4.6/(20/4) | | 7/9-11/60 | | xy^2+xz^2=0 | | 3x+1=8-x/2 | | .6666(6c+4)-(8c-5)=0 | | (25x)^(3/2)-125 | | 1-70n=7(1-10n) | | Z-2.05=1.95 | | x+3x+5=4(x+1) | | Z-2.05=1.85 |